Intestinal microbiota and melatonin in the treatment of secondary injury and complications after spinal cord injury - Zhang, Yiwen; Lang, Rui; Guo, Shunyu; Luo, Xiaoqin; Li, Huiting; Liu, Cencen; Dong, Wei; Bao, Changshun; Yu, Yang (Frontiers in Neuroscience, 2022)
Spinal cord injury (SCI) is a central nervous system (CNS) disease that can cause the impairment of sensory and motor below the level of injury. At present, the treatment scheme for SCI mainly focused on secondary injury and complications. Recent studies have shown that SCI leads to an imbalance of intestinal microbiota and the imbalance is also associated with complications after SCI, possibly through the microbial-brain-gut axis. Melatonin is secreted in many parts of the body including pineal gland and gut, it is effective in protecting the spinal cord from secondary damage. The secretion of melatonin is affected by circadian rhythms, known as the dark light cycle, and SCI would cause dysregulation of melatonin secretion as well. In addition, melatonin is closely related to the intestinal microbiota, which protects the barrier function of the gut through its antioxidant and anti-inflammatory effects, and increases the abundance of intestinal microbiota by influencing the metabolism of the intestinal microbiota. Furthermore, the intestinal microbiota can influence melatonin formation by regulating the metabolism of tryptophan and serotonin. This paper summarises and reviews the knowledge on the relationship among intestinal microbiota, melatonin and SCI, with the aim of providing new theories and ideas for clinical research related to spinal cord injury treatment.